PA56 composite material as well as preparation method and application thereof

By combining PA56 resin with copolyamide, toughener, lubricant and antioxidant in a specific proportion, PA56 composite material with excellent toughness and weather resistance was prepared, which solved the problem of poor weather resistance of nylon 56 and achieved the correctness of 100% Widely used in areas where weather resistance is required.

CN119410142APending Publication Date: 2025-02-11JIANGSU KINGFA SCI & TECH ADVANCED MATERIALS CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411737117.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Nylon 56 has poor weather resistance and is prone to yellowing in the sun, affecting its appearance and service life, and limiting its application in areas with requirements for weather resistance.

Method used

By combining PA56 resin with copolyamide, toughener, lubricant and antioxidant in a specific proportion, PA56 composite material with excellent toughness and weather resistance was prepared.

Benefits of technology

It improves the impact toughness and weather resistance of the material, making it suitable for automotive parts, portable tools, tents and other fields, especially for the preparation of automotive parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a PA56 composite material as well as a preparation method and application thereof, and belongs to the technical field of high polymer materials, the PA56 composite material comprises the following components in parts by weight: 38-92 parts of PA56 resin, 4-32 parts of copolymerized polyamide, 4-32 parts of a flexibilizer, 0.3-2 parts of a lubricant and 0.1-2 parts of an antioxidant; the copolymerized polyamide comprises repeating structural units derived from a diamine and a diacid; the diamine comprises 2-methyl-pentamethylene diamine; the diacid comprises at least one of adipic acid, terephthalic acid and isophthalic acid. The PA56 composite material disclosed by the invention has excellent toughness and weather resistance, can be widely applied to the fields of automobile parts, carrying tools and tents which have relatively high requirements on weather resistance and toughness, and is particularly suitable for preparing the automobile parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a PA56 composite material and a preparation method and application thereof. Background Art

[0002] Nylon 56 (PA56) is a new type of bio-based polyamide polymerized from bio-based pentamethylenediamine and petroleum-based adipic acid. The main chain of nylon 56 is connected by amide bonds to several repeating units, and the ends of the molecular chain are carboxyl and amino groups. The bio-based pentamethylenediamine of nylon 56 comes from natural organisms, such as corn or other starch-containing substances. After starch is decomposed into glucose, microorganisms modified by bioengineering technology act on lysine to decarboxylate it to obtain pentamethylenediamine. This preparation method of bio-based pentamethylenediamine reduces production costs, alleviates the pressure of shortage of petroleum resources, and makes nylon 56 a competitive nylon material.

[0003] Nylon 56 has great application potential in the automotive industry, and PA56 can be used as a typical carbon reduction material. However, although PA56 has a wide range of applications in the fields of carrying equipment, tents, glass products, casting injection molding, wear-resistant plastics, etc., nylon 56 has poor weather resistance and is easy to turn yellow in the sun, affecting its appearance and service life, limiting its application in fields that require weather resistance. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a PA56 composite material and a preparation method and application thereof, wherein the PA56 composite material has excellent toughness and weather resistance.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A PA56 composite material comprises the following components in parts by weight: 38 to 92 parts of PA56 resin, 4 to 32 parts of copolymerized polyamide, 4 to 32 parts of toughening agent, 0.3 to 2 parts of lubricant, and 0.1 to 2 parts of antioxidant;

[0007] The copolyamide comprises repeating structural units derived from diamine and diacid; the diamine comprises 2-methyl-pentanediamine; and the diacid comprises at least one of adipic acid, terephthalic acid, and isophthalic acid.

[0008] The present invention creatively combines the above-mentioned raw materials in parts by weight to obtain a PA56 composite material with excellent toughness and weather resistance. The PA56 composite material can be widely used in fields such as automotive parts, carrying equipment, tents, etc. that have high requirements for weather resistance and toughness, and is especially suitable for the preparation of automotive parts.

[0009] Preferably, 2-methyl-pentanediamine accounts for 5 to 60% based on the molar amount of all diamines.

[0010] The present invention uses a specific type of copolymerized polyamide, so it has good weather resistance, and the reduction of amide groups destroys the molecular weight regularity of nylon to a certain extent, expands the molecular chain spacing, and thus improves the impact toughness of the material. In the PA56 composite material, it can play a dual role of improving the weather resistance and toughness of the material.

[0011] The amount of the PA56 resin is 38 to 92 parts, for example, 38 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 92 parts or a range consisting of any two of these values.

[0012] Preferably, the PA56 resin is used in an amount of 40 to 90 parts.

[0013] The amount of the copolyamide is 4 to 32 parts, for example, 4 parts, 5 parts, 8 parts, 10 parts, 15 parts, 20 parts, 30 parts, 32 parts or a range consisting of any two of these values.

[0014] Preferably, the amount of the copolyamide is 5 to 30 parts.

[0015] The amount of the toughening agent is 4 to 32 parts, for example, 4 parts, 5 parts, 8 parts, 10 parts, 15 parts, 20 parts, 30 parts, 32 parts or a range consisting of any two of these values.

[0016] Preferably, the toughening agent is used in an amount of 5 to 30 parts.

[0017] The amount of the lubricant is 0.3 to 2 parts, for example, 0.3 parts, 0.5 parts, 0.8 parts, 1 part, 1.5 parts, 2 parts or a range consisting of any two of these values.

[0018] The amount of the antioxidant is 0.1 to 2 parts, for example, 0.1 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1 parts, 1.5 parts, 2 parts or a range consisting of any two of these values.

[0019] Wherein, in the PA56 composite material of the present invention, the weight percentage of the PA56 resin is not less than 50%.

[0020] Preferably, in the PA56 composite material of the present invention, the weight percentage of the PA56 resin is 55-80%.

[0021] Preferably, the PA56 composite material comprises the following components in parts by weight: 40 to 90 parts of PA56 resin, 5 to 30 parts of copolymerized polyamide, 5 to 30 parts of toughening agent, 0.3 to 2 parts of lubricant, and 0.1 to 2 parts of antioxidant.

[0022] Preferably, the PA56 composite material comprises the following components in parts by weight: 60 to 80 parts of PA56 resin, 10 to 20 parts of copolymerized polyamide, 5 to 10 parts of toughening agent, 0.8 to 1.5 parts of lubricant, and 0.5 to 1.2 parts of antioxidant.

[0023] Preferably, the copolymer polyamide is at least one of polyhexamethylene adipamide / poly-2-methyl-pentamethylene isophthalamide, polyhexamethylene adipamide / poly-2-methyl-pentamethylene adipamide, polyhexamethylene adipamide / poly-2-methyl-pentamethylene terephthalamide, polyhexamethylene terephthalamide / poly-2-methyl-pentamethylene isophthalamide, polyhexamethylene terephthalamide / poly-2-methyl-pentamethylene adipamide, and polyhexamethylene terephthalamide / poly-2-methyl-pentamethylene terephthalamide.

[0024] Preferably, the copolymerized polyamide is at least one of polyhexamethylene adipamide / poly(2-methyl-isophthalamide)pentamethylenediamine and poly(hexamethylene terephthalamide) / poly(2-methyl-isophthalamide)pentamethylenediamine.

[0025] Preferably, at least one of the following (a) to (f) is satisfied:

[0026] (a) in the poly(hexamethylene adipamide) / poly(2-methyl-isophthalamide)-pentamethylenediamine, the molar percentage of the poly(2-methyl-isophthalamide)-pentamethylenediamine chain segment is 5 to 50%;

[0027] (b) in the polyhexamethylene adipamide / poly-2-methyl-pentamethylene adipamide, the molar percentage of the poly-2-methyl-pentamethylene adipamide chain segment is 5 to 50%;

[0028] (c) in the polyhexamethylene adipamide / poly(2-methyl-pentamethylene terephthalamide), the molar percentage of the poly(2-methyl-pentamethylene terephthalamide) chain segment is 5 to 50%;

[0029] (d) in the poly(hexamethylene terephthalamide) / poly(2-methyl-isophthalamide)-pentamethylenediamine, the molar percentage of the poly(2-methyl-isophthalamide)-pentamethylenediamine chain segment is 5 to 50%;

[0030] (e) in the poly(hexamethylene terephthalamide) / poly(2-methyl-pentamethylene adipamide) the molar percentage of the poly(2-methyl-pentamethylene adipamide) chain segment is 5 to 50%;

[0031] (f) In the poly(hexamethylene terephthalamide) / poly(2-methyl-pentamethylene terephthalamide) the molar percentage of the poly(2-methyl-pentamethylene terephthalamide) chain segment is 5 to 50%.

[0032] The present invention optimizes the toughness and weather resistance of the material by controlling the molar percentage of the polyisophthalamide-2-methyl-pentanediamine segment, the polyadipamide-2-methyl-pentanediamine segment, and the polyterephthalamide-2-methyl-pentanediamine segment in the copolymer polyamide. If the molar percentage is low, the effect of reducing the content of the amide group is not obvious, and the effect of expanding the distance between the nylon molecular chains is not obvious, so the effect of improving weather resistance and toughening is not obvious. If the molar percentage is too high, the compatibility of the copolymer polyamide and PA56 will be reduced, and the use value will be lost.

[0033] More preferably, 2-methylpentanediamine accounts for 5 to 50% based on the molar amount of all diamines.

[0034] Preferably, in the polyhexamethylene adipamide / polyisophthalamide-2-methyl-pentamethylenediamine, the molar percentage of the polyisophthalamide-2-methyl-pentamethylenediamine chain segment is 10 to 30%;

[0035] Preferably, in the polyhexamethylene adipamide / poly-2-methyl-pentamethylene adipamide, the molar percentage of the poly-2-methyl-pentamethylene adipamide chain segment is 10 to 30%;

[0036] Preferably, in the polyhexamethylene adipamide / poly(2-methyl-pentamethylene terephthalamide), the molar percentage of the poly(2-methyl-pentamethylene terephthalamide) chain segment is 10 to 30%;

[0037] Preferably, in the poly(hexamethylene terephthalamide) / poly(2-methyl-isophthalamide)-pentamethylenediamine, the molar percentage of the poly(2-methyl-isophthalamide)-pentamethylenediamine chain segment is 10 to 30%;

[0038] Preferably, in the poly(hexamethylene terephthalamide) / poly(2-methyl-adipamide)-pentamethylenediamine, the molar percentage of the poly(2-methyl-adipamide)-pentamethylenediamine chain segment is 10 to 30%;

[0039] Preferably, in the poly(hexamethylene terephthalamide) / poly(2-methyl-pentamethylene terephthalamide) chain segment, the molar percentage of the poly(2-methyl-pentamethylene terephthalamide) chain segment is 10-30%.

[0040] It should be noted that the present invention is not limited to the source of the copolyamide, and the copolyamide described in the present invention can be a commercially available product or can be homemade.

[0041] Exemplarily, the homemade method of the copolyamide is as follows:

[0042] In a pressure autoclave equipped with magnetic coupling stirring, condenser, gas phase port, feed port and pressure explosion-proof port, the reaction raw materials (diamine and diacid) are added in a specific proportion. Then, benzoic acid, sodium hypophosphite (as a catalyst) and deionized water are added. The amount of benzoic acid is 2-3% of the total mass of diamine and diacid, the weight of sodium hypophosphite is 0.05-0.15% of the other feed weight except deionized water, and the weight of deionized water is 20-40% of the total feed weight. Under stirring, vacuum is first evacuated, and then high-purity nitrogen is used as a protective gas to raise the temperature to 215-225°C within 1.5-2.5 hours. The reaction mixture is stirred at 215-225°C for 0.5-2 hours, and then stirring is continued to raise the temperature of the reactants to 255-265°C, and the reaction is continued at a constant temperature and a constant pressure of 2.1-2.3MPa for 1.5-3 hours, and the pressure is kept stable by continuously removing the generated water. After the reaction is completed, the product is discharged. The prepolymer is vacuum dried at 75-85° C. to obtain a prepolymer product. Then, the prepolymer product is solid-phase thickened at 225-235° C. and 40-60 Pa vacuum conditions for 8-12 hours to finally obtain a copolymer polyamide.

[0043] Preferably, the toughening agent includes at least one of POE grafted GMA and MAH grafted rubber;

[0044] The rubber is a polyolefin rubber; the polyolefin rubber includes at least one of saturated polyolefin rubber and unsaturated polyolefin rubber; the saturated polyolefin rubber includes ethylene-octene copolymer, polyethylene rubber, polypropylene rubber, polyisobutylene rubber, ethylene-propylene rubber, linear low-density polyethylene rubber, ethylene-butene rubber, and vinyl chloride rubber; the unsaturated polyolefin rubber is selected from at least one of ethylene propylene diene monomer rubber, butadiene-styrene rubber, styrene-ethylene-butadiene-styrene block copolymer, ethylene-propylene-butadiene rubber, styrene-butadiene-styrene copolymer, and styrene-isoprene copolymer.

[0045] Preferably, the toughening agent includes POE grafted GMA and MAH grafted rubber; the weight ratio of the POE grafted GMA to the MAH grafted rubber is 1:(0.5-2).

[0046] The present invention creatively adopts POE grafted GMA and MAH grafted rubber as toughening agents, effectively improving the interface strength between different components in the material, improving the material compatibility, and can significantly improve the toughness and weather resistance without using glass fiber and nucleating agent.

[0047] Preferably, the grafting rate of GMA in the POE-grafted GMA is 0.2-1.5%, for example, it can be 0.2%, 0.3%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5% or a range consisting of any two values ​​therein.

[0048] Preferably, the grafting rate of GMA in the POE-grafted GMA is 0.5-1%.

[0049] POE grafted GMA can be a commercially available product or homemade.

[0050] Exemplary, the preparation method of POE grafted GMA (homemade method): POE, GMA, initiator and other raw materials are mixed evenly in proportion, added to single-screw extruder, twin-screw extruder, internal mixer and other processing equipment for melt blending, the extruded grafted material is cooled and granulated, the melt blending temperature is 130-200°C, and the rotation speed is 200-500rpm.

[0051] The initiator can be dicumyl peroxide or dibenzoyl peroxide, and the amount used is not higher than 0.3% of the total feed weight.

[0052] The grafting rate of GMA is controlled by controlling the added amounts of POE and GMA.

[0053] Among them, the test method for the grafting rate of GMA in POE grafted GMA is: weigh 0.5g of the sample and dissolve it in 70mL of xylene, then add 10mL of 0.5mol / L trichloroacetic acid-xylene standard solution, heat and reflux for 2h, add 2 drops of phenolphthalein indicator (10g / L), titrate to the end point with 0.5mol / L KOH-ethanol standard solution, and do a blank test.

[0054] The grafting rate r is calculated according to the following formula: r = c × (V0-V1) × 142.15 / (1000 × m) × 100%.

[0055] Wherein: c is the concentration of KOH-ethanol standard solution (mol / L); V0 is the volume of standard solution consumed in blank titration (mL); V1 is the volume of standard solution consumed in titration (mL); 142.15 is the relative molecular mass of GMA; m is the mass of the sample (g).

[0056] The POE (polyolefin thermoplastic elastomer) mentioned in the present invention is a thermoplastic elastomer obtained by in-situ polymerization of ethylene and α-olefin using a metallocene catalyst, wherein the α-olefin includes at least one of α-olefins having 4 to 8 carbon atoms.

[0057] Preferably, the α-olefin includes at least one of 1-butene, 1-hexene and 1-octene.

[0058] Furthermore, the POE is preferably a thermoplastic elastomer obtained by in-situ polymerization of ethylene and 1-octene using a metallocene catalyst.

[0059] Preferably, the melt flow rate of the POE grafted GMA at 190°C / 2.16kg is 4-15g / 10min, for example, 4g / 10min, 6g / 10min, 8g / 10min, 10g / 10min, 12g / 10min, 15g / 10min or a range consisting of any two of these values.

[0060] Preferably, the melt flow rate of the POE grafted GMA at 190° C. / 2.16 kg is 4 to 12 g / 10 min.

[0061] The melt flow rate of the POE grafted GMA of the present invention is obtained by testing according to ISO-1133.

[0062] Preferably, the grafting rate of MAH in the MAH grafted rubber is 0.1-3%, for example, 0.1%, 0.5%, 1%, 2%, 3% or a range consisting of any two of these values.

[0063] Preferably, the grafting rate of MAH in the MAH grafted rubber is 0.5-2%.

[0064] The MAH grafted rubber can be a commercial product or homemade.

[0065] Exemplarily, the MAH grafted rubber preparation method (homemade method) is as follows: a single-screw extruder, a twin-screw extruder, an internal mixer and other processing equipment are used to react and complete the melt grafting of the rubber component, and a grafting monomer (maleic anhydride) is added to the molten rubber. The reaction temperature is 150-200°C, the rotation speed is 200-500rpm, and the concentration of the reaction monomer is controlled. Initiators such as diisopropyl peroxide and dibenzoyl peroxide can be selected, and the amount used is not more than 0.3% of the total feed weight.

[0066] The grafting rate of MAH in the present invention can be determined by infrared spectroscopy: a sample of fixed thickness is tested by Fourier infrared spectrometer to obtain characteristic absorption peaks of infrared spectrum, and the grafting rate of maleic anhydride can be calculated by comparing the ratio of carbonyl and methylene absorption intensities.

[0067] Preferably, the lubricant is rice bran wax, and the acid value of the rice bran wax is ≤90 mgKOH / g.

[0068] Preferably, the acid value of the rice bran wax is ≤85 mgKOH / g.

[0069] Preferably, the acid value of the rice bran wax is 15 to 85 mgKOH / g.

[0070] Preferably, the acid value of the rice bran wax is 15 to 55 mgKOH / g.

[0071] Preferably, the average particle size of the rice bran wax is 4 to 30 μm.

[0072] Wherein, the acid value of the rice bran wax described in the present invention is tested and obtained according to the method of GB / T 5530.

[0073] Preferably, the relative viscosity of the PA56 resin is 2.0-3.2, for example, it can be 2.0, 2.2, 2.5, 2.8, 3.0, 3.2 or a range consisting of any two of these values.

[0074] Preferably, the relative viscosity of the copolymerized polyamide is 1.8-3, for example, 1.8, 2, 2.2, 2.4, 2.5, 2.6, 2.8, 3 or a range consisting of any two of these values.

[0075] The relative viscosity of the PA56 resin and copolymerized polyamide of the present invention is tested according to the test standard ISO307-2010. The specific test parameters include: the relative viscosity η of the nylon prepolymer with a concentration of 0.25 g / dl is measured in 98% concentrated sulfuric acid at 25±0.01°C. r Preferably, the antioxidant is at least one of a thioether antioxidant, a polyaromatic amine antioxidant, and a hindered amine antioxidant.

[0076] Preferably, the PA56 composite material of the present invention may include 0.1 to 10 parts of additives.

[0077] Preferably, the auxiliary agent includes at least one of a pigment, a flame retardant, a filler, an ultraviolet light absorber, and an antistatic agent.

[0078] The PA56 composite material described in the present invention may include pigments, and suitable pigments include but are not limited to carbon black, titanium dioxide, zinc sulfide, ultramarine, titanium yellow, iron yellow, iron red, cobalt blue, iron black, azo pigments, phthalocyanine pigments, dioxazine pigments, quinacridone pigments, isoindoline pigments, isoindolinone pigments, perylene pigments, quinophthalone pigments, anthraquinone pigments and combinations thereof.

[0079] The PA56 composite material described in the present invention may include a flame retardant, and suitable flame retardants include but are not limited to brominated polymers (e.g., brominated polystyrene), metal dialkyl phosphites (e.g., tris(diethylphosphite) aluminum), metal hydroxides (e.g., magnesium hydroxide), aromatic phosphates (e.g., resorcinol di(diphenyl phosphate) ester and bisphenol A di(diphenyl phosphate) ester), and combinations thereof.

[0080] The PA56 composite material of the present invention may include a filler, and suitable fillers include but are not limited to silicon dioxide, calcium carbonate, talc, wollastonite, glass balls, kaolin, single crystal fibers, carbon fibers, glass fibers, barium sulfate, and combinations thereof.

[0081] The PA56 composite material of the present invention may include a UV absorber, and suitable UV absorbers include but are not limited to hydroxybenzophenones, hydroxybenzotriazoles, hydroxybenzotriazines, cyanoacrylates, nanoscale inorganic materials (eg, titanium oxide, cerium oxide, and zinc oxide), and combinations thereof.

[0082] The PA56 composite material of the present invention may include an antistatic agent. Suitable antistatic agents include but are not limited to zinc oxide, manganese dioxide, chromium trioxide and combinations thereof.

[0083] The present invention also provides a method for preparing a PA56 composite material, comprising the following steps:

[0084] The components are mixed evenly, and then extruded and granulated by a twin-screw extruder to obtain a PA56 composite material.

[0085] The present invention also provides an application of the PA56 composite material in the preparation of automobile parts, carrying equipment and tents.

[0086] The beneficial effects of the present invention are as follows: the PA56 composite material of the present invention has excellent toughness and weather resistance, and the PA56 composite material can be widely used in fields such as automotive parts, carrying equipment, tents, etc. that have high requirements on weather resistance and toughness, and is especially suitable for the preparation of automotive parts. DETAILED DESCRIPTION

[0087] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0088] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0089] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0090] The raw materials used in the embodiments and comparative examples are described as follows:

[0091] PA56-1: relative viscosity is 2.8, Cathay Biotechnology, brand: E-1273.

[0092] PA56-2: relative viscosity is 2.6, Cathay Biotechnology, brand: E-2260.

[0093] PA6T / 66: relative viscosity is 2.3, INVISTA, brand: NPD-652.

[0094] MAH grafted rubber-1: maleic anhydride grafted butadiene-styrene rubber, the butadiene-styrene rubber is SBR1502 (Shandong Haifang Rubber), the maleic anhydride grafting rate is 0.5%, and it is homemade.

[0095] MAH grafted rubber-2: maleic anhydride grafted butadiene-styrene rubber, the butadiene-styrene rubber is SBR1502 (Shandong Haifang Rubber), the maleic anhydride grafting rate is 2%, and it is homemade.

[0096] MAH grafted rubber-3: maleic anhydride grafted butadiene-styrene rubber, the butadiene-styrene rubber is SBR1502 (Shandong Haifang Rubber), the maleic anhydride grafting rate is 0.1%, and it is homemade.

[0097] MAH grafted rubber-4: maleic anhydride grafted butadiene-styrene rubber, the butadiene-styrene rubber is SBR1502 (Shandong Haifang Rubber), the maleic anhydride grafting rate is 3%, and it is homemade.

[0098] MAH grafted rubber-5: maleic anhydride grafted polyethylene rubber, maleic anhydride grafting rate is 0.5%, homemade.

[0099] MAH grafted rubber-6: maleic anhydride grafted butadiene-acrylonitrile rubber, butadiene-acrylonitrile rubber is derived from Chemigum P35 (35% acrylonitrile), produced in Ilio, France, maleic anhydride grafting rate is 0.5%, homemade.

[0100] Butadiene-styrene rubber: Shandong Haifang Rubber, SBR1502.

[0101] POE: Dow Chemical, brand: POE 8137.

[0102] POE grafted GMA-1: The grafting rate of GMA is 1%, POE comes from Dow Chemical, brand: POE 8137, homemade.

[0103] POE grafted GMA-2: The grafting rate of GMA is 0.5%, POE comes from Dow Chemical, brand: POE 8137, and is homemade.

[0104] POE grafted GMA-3: The grafting rate of GMA is 0.2%, POE comes from Dow Chemical, brand: POE 8137, and is homemade.

[0105] POE grafted GMA-4: The grafting rate of GMA is 2%, POE comes from Dow Chemical, brand: POE 8137, homemade.

[0106] Rice bran wax-1: acid value is 55mgKOH / g, Chongqing Hecai Chemical Technology Co., Ltd., brand: Bio-M803.

[0107] Rice bran wax-2: acid value is 15mgKOH / g, Chongqing Hecai Chemical Technology Co., Ltd., brand: Bio-M804.

[0108] Rice bran wax-3: acid value is 85mgKOH / g, Chongqing Hecai Chemical Technology Co., Ltd., brand: Bio-M802.

[0109] Antioxidant: Antioxidant 1010 and antioxidant 264 are compounded in a weight ratio of 1:1.

[0110] Poly(hexamethylene adipamide) / poly(2-methyl-isophthalamide)-1 (PA66 / DI-1 for short), wherein the molar percentage of the poly(2-methyl-isophthalamide)-11 chain segment is 10%.

[0111] Poly(hexamethylene adipamide) / poly(2-methyl-isophthalamide)-pentamethylenediamine-2 (PA66 / DI-2 for short), wherein the molar percentage of the poly(2-methyl-isophthalamide)-pentamethylenediamine chain segment is 30%.

[0112] Poly(hexamethylene adipamide) / poly(2-methyl-isophthalamide)-pentamethylenediamine-3 (PA66 / DI-3 for short), wherein the molar percentage of the poly(2-methyl-isophthalamide)-pentamethylenediamine chain segment is 5%.

[0113] Poly(hexamethylene adipamide) / poly(2-methyl-isophthalamide)-pentamethylenediamine-4 (PA66 / DI-4 for short), wherein the molar percentage of the poly(2-methyl-isophthalamide)-pentamethylenediamine chain segment is 50%.

[0114] Poly(hexamethylene adipamide) / poly(2-methyl-isophthalamide)-pentamethylenediamine-6 ​​(PA66 / DI-6 for short), wherein the molar percentage of the poly(2-methyl-isophthalamide)-pentamethylenediamine chain segment is 60%.

[0115] Polyhexamethylene adipamide / poly-2-methyl-pentamethylene adipamide (PA66 / D6 for short), the molar percentage of poly-2-methyl-pentamethylene adipamide is 10%.

[0116] Polyhexamethylene adipamide / poly-2-methyl-pentamethylene terephthalamide (PA66 / DT for short), wherein the molar percentage of poly-2-methyl-pentamethylene terephthalamide is 10%.

[0117] Poly(hexamethylene terephthalamide) / poly(2-methyl-isophthalamide)-pentamethylenediamine (PA6T / DI for short), wherein the molar percentage of poly(2-methyl-isophthalamide)-pentamethylenediamine is 10%.

[0118] Polyhexamethylene terephthalamide / poly(2-methyl-adipamide) (PA6T / D6 for short): the molar percentage of poly(2-methyl-adipamide) is 10%.

[0119] Polyhexamethylene terephthalamide / poly-2-methyl-pentamethylene terephthalamide (PA6T / DT for short): the molar percentage of poly-2-methyl-pentamethylene terephthalamide is 10%.

[0120] Among them, the homemade methods of PA66 / DI-1~6, PA66 / D6, PA66 / DT, PA6T / DI, PA6T / D6, and PA6T / DT are as follows:

[0121] In a pressure autoclave equipped with magnetic coupling stirring, condenser, gas phase port, feed port and pressure explosion-proof port, the reaction raw materials (diamine and diacid) are added in a specific proportion. Then, benzoic acid, sodium hypophosphite (as a catalyst) and deionized water are added. The amount of benzoic acid is 2.5% of the total mass of diamine and diacid, the weight of sodium hypophosphite is 0.1% of the other feed weight except deionized water, and the weight of deionized water is 30% of the total feed weight. Under stirring, vacuum is first evacuated, and then high-purity nitrogen is used as a protective gas to raise the temperature to 220°C within 2 hours. The reaction mixture is stirred at 220°C for 1 hour, and then stirring is continued to raise the temperature of the reactants to 255-265°C, and the reaction is continued at a constant temperature and a constant pressure of 2.2MPa for 2 hours, and the pressure is kept stable by continuously removing the generated water. After the reaction is completed, the product is discharged. The prepolymer is vacuum dried at 80°C for 24 hours to obtain a prepolymer product. Then, the prepolymerized product was solid-phase thickened at 230° C. and 50 Pa vacuum conditions for 10 hours to finally obtain copolymer polyamide.

[0122] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0123] Examples 1 to 30, Comparative Examples 1 to 2

[0124] The formulations of the PA56 composite materials of Examples 1 to 30 and Comparative Examples 1 to 2 are shown in Tables 1 and 2 (all in the tables are parts by weight).

[0125] The preparation methods of the PA56 composite materials of Examples 1 to 30 and Comparative Examples 1 to 2 all include the following steps:

[0126] The components are mixed evenly, and then extruded and granulated through a twin-screw extruder to obtain a PA56 composite material, wherein the twin-screw extruder is set at a temperature of 220-280° C. and a screw speed of 400 rpm.

[0127] Table 1

[0128]

[0129]

[0130] Table 2

[0131]

[0132] Performance Testing

[0133] Notched impact strength: Izod notched impact strength (A-notch): according to ISO 180-2000, 4mm, 23°C.

[0134] Weathering test: tested according to VS-99.01-L-08004 interior test method, irradiation energy 488KJ / m 2 , the time is 24*7h, and the color difference ΔE is determined in SCE mode.

[0135] Table 3

[0136] <![CDATA[Notched impact strength / kJ / m 2 > ΔE Example 1 19.2 2.34 Example 2 18.3 2.44 Example 3 22.2 1.31 Example 4 22.3 1.42 Example 5 23.5 1.41 Example 6 22.0 1.43 Example 7 18.1 2.35 Example 8 17.3 2.55 Example 9 14.5 3.37 Example 10 23.0 1.32 Embodiment 11 24.3 1.38 Example 12 21.9 1.32 Embodiment 13 22.6 1.30 Embodiment 14 23.5 1.43 Embodiment 15 24.3 1.43 Example 16 16.9 2.72 Embodiment 17 18.1 2.56 Embodiment 18 11.2 3.45 Embodiment 19 12.2 3.55 Embodiment 20 23.3 1.33 Embodiment 21 16.8 2.64 Embodiment 22 17.9 2.42 Embodiment 23 17.2 2.77 Embodiment 24 16.0 2.65 Embodiment 25 10.8 3.81 Embodiment 26 11.2 3.88 Embodiment 27 16.3 3.15 Embodiment 28 14.3 3.31 Embodiment 29 23.5 1.33 Embodiment 30 15.1 3.22 Comparative Example 1 7.4 4.52 Comparative Example 2 8.2 4.33

[0137] It can be seen from Table 3 that the PA56 composite material of the present invention has excellent toughness and weather resistance, wherein the notched impact strength of the PA56 composite material of the present invention is ≥10.8 kJ / m 2 , ΔE≤3.88.

[0138] It can be seen from the comparison of the embodiment and comparative examples 1 to 2 that the copolymerized polyamide of the present invention can significantly improve the impact toughness and weather resistance of the PA56 composite material.

[0139] By comparing Examples 2 and 3 with Examples 1 and 4, it can be seen that the impact toughness and weather resistance are further improved by controlling the weight of each raw material to: 60 to 80 parts of PA56 resin, 10 to 20 parts of copolymerized polyamide, 5 to 10 parts of toughening agent, 0.8 to 1.5 parts of lubricant, and 0.5 to 1.2 parts of antioxidant.

[0140] By comparing Examples 3, 6 to 10, it can be seen that by controlling the molar percentage of DI units in PA66 / DI to 10 to 50%, the impact toughness and weather resistance are further improved, and by controlling the molar percentage of DI units in PA66 / DI to 10 to 30, the impact toughness and weather resistance are further improved.

[0141] Comparative Examples 3 and 15 to 17 show that by controlling the MAH content in the MAH grafted rubber to 0.5 to 2%, the impact toughness and weather resistance are further improved.

[0142] Comparative Examples 3, 20, 21 and 22 show that by controlling the GMA content in the POE grafted GMA to 0.5-1%, the impact toughness and weather resistance are further improved.

[0143] Comparative Examples 3 and 23 to 26 show that by controlling the weight ratio of the POE grafted GMA to the MAH grafted rubber to be 1:(0.5 to 2), the impact toughness and weather resistance are further improved.

[0144] Comparative Examples 3, 29 and 30 show that the impact toughness and weather resistance are further improved by using rice bran wax having an acid value of 15 to 55 mgKOH / g.

[0145] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A PA56 composite material, characterized in that: The invention comprises the following components in parts by weight: 38 to 92 parts of PA56 resin, 4 to 32 parts of copolymerized polyamide, 4 to 32 parts of toughening agent, 0.3 to 2 parts of lubricant, and 0.1 to 2 parts of antioxidant; The copolyamide comprises repeating structural units derived from diamine and diacid; the diamine comprises 2-methyl-pentanediamine; and the diacid comprises at least one of adipic acid, terephthalic acid, and isophthalic acid.

2. The PA56 composite material according to claim 1, characterized in that: The copolymer polyamide is at least one of polyhexamethylene adipamide / polyisophthalamide-2-methyl-pentamethylenediamine, polyhexamethylene adipamide / polyisophthalamide-2-methyl-pentamethylenediamine, polyhexamethylene adipamide / poly2-methyl-pentamethylenediamine, polyhexamethylene terephthalamide / polyisophthalamide-2-methyl-pentamethylenediamine, polyhexamethylene terephthalamide / poly2-methyl-pentamethylenediamine, and polyhexamethylene terephthalamide / poly2-methyl-pentamethylenediamine.

3. The PA56 composite material according to claim 2, characterized in that: Satisfy at least one of the following (a) to (f): (a) in the poly(hexamethylene adipamide) / poly(2-methyl-isophthalamide)-pentamethylenediamine, the molar percentage of the poly(2-methyl-isophthalamide)-pentamethylenediamine chain segment is 5 to 50%; (b) in the polyhexamethylene adipamide / poly-2-methyl-pentamethylene adipamide, the molar percentage of the poly-2-methyl-pentamethylene adipamide chain segment is 5 to 50%; (c) in the polyhexamethylene adipamide / poly(2-methyl-pentamethylene terephthalamide), the molar percentage of poly(2-methyl-pentamethylene terephthalamide) is 5 to 50%; (d) in the poly(hexamethylene terephthalamide) / poly(2-methyl-isophthalamide)-pentamethylenediamine, the molar percentage of the poly(2-methyl-isophthalamide)-pentamethylenediamine chain segment is 5 to 50%; (e) in the poly(hexamethylene terephthalamide) / poly(2-methyl-pentamethylene adipamide) the molar percentage of the poly(2-methyl-pentamethylene adipamide) chain segment is 5 to 50%; (f) In the poly(hexamethylene terephthalamide) / poly(2-methyl-pentamethylene terephthalamide), the molar percentage of poly(2-methyl-pentamethylene terephthalamide) is 5 to 50%.

4. The PA56 composite material according to claim 1, characterized in that: The toughening agent includes at least one of POE grafted GMA and MAH grafted rubber; The rubber is a polyolefin rubber; the polyolefin rubber includes at least one of saturated polyolefin rubber and unsaturated polyolefin rubber; the saturated polyolefin rubber includes ethylene-octene copolymer, polyethylene rubber, polypropylene rubber, polyisobutylene rubber, ethylene-propylene rubber, linear low-density polyethylene rubber, ethylene-butene rubber, and vinyl chloride rubber; the unsaturated polyolefin rubber is selected from at least one of ethylene propylene diene monomer rubber, butadiene-styrene rubber, styrene-ethylene-butadiene-styrene block copolymer, ethylene-propylene-butadiene rubber, styrene-butadiene-styrene copolymer, and styrene-isoprene copolymer.

5. The PA56 composite material according to claim 4, characterized in that: The toughening agent includes POE grafted GMA and MAH grafted rubber; the weight ratio of the POE grafted GMA to the MAH grafted rubber is 1:(0.5-2).

6. The PA56 composite material according to claim 4, characterized in that: The grafting rate of GMA in the POE-grafted GMA is 0.2-1.5%.

7. The PA56 composite material according to claim 4, characterized in that: The grafting rate of MAH in the MAH grafted rubber is 0.1-3%.

8. The PA56 composite material according to claim 1, characterized in that: The lubricant is rice bran wax, and the acid value of the rice bran wax is ≤90 mgKOH / g.

9. The method for preparing the PA56 composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The components are mixed evenly, and then extruded and granulated by a twin-screw extruder to obtain a PA56 composite material.

10. Use of the PA56 composite material according to any one of claims 1 to 8 in the preparation of automobile parts, carrying equipment and tents.

Citation Information

Cited By

  • Polyamide composite material, method for preparing same, and use thereof

    WO2026179434A1